A flecha mata porque tem vida: um estudo etnográfico sobre os artefatos de caça dos Gavião Ikólóéhj - Bento, Rodolpho Claret (Universidade Federal de São Carlos, 2013)
This work aims to elucidate the relationships the Gavião people of Rondônia engaged when manufacturing and using of hunting artefacts. From an ethnographic approach, I explore pertinent notions to comprehend the agency of warfare objects, hunters, dogs, and enunciations in hunting activity. I develop a parallel between the manufacturing of artefacts bodies and the constitution of artifactual anatomies of men, wishing problematize how encounters between bodies and materials (or substances) conforms the effectiveness of hunters and their hunting instruments. If into Gavião s discourse the arrow kills because has life , I propose to think what is that concept of vitality and the relationships produced about this assumption. It is a challenge outlined by a biographical study of the hunting artefacts, that is presented as an interlacement of vital forces in the interactions between humans, animals, spirits and objects.
Keywords: Etnologia; Antropologia social; Rondônia; Cinegética; Biografia; Gavião Ikólóéhj; Artefatos; Caça; Artefacts; Hunting; Ethnology; CIENCIAS HUMANAS::ANTROPOLOGIA